Report about star fruit fruits damaged by Amazona albifrons Sparman, in Tabasco, Mexico. - Sánchez-Soto, Saúl (Agronomía Mesoamericana, 2016)
The aim of this study was to determine, the animal species causing damage to inmature fruits ofAverrhoa carambola, in a home garden. The study was conducted in a home garden with two star fruit trees in Cardenas, Tabasco, Mexico (18°00’10.9’’ N, 93°25’52.2’’ W). The loss of fruits was registered from June 21st to August 2nd, 2015 based on weekly evaluations. 12 637 fruits were toppled by the bird Amazona albifrons Sparman (Psitaciformes: Psittacidae), which is distributed from Mexico to Costa Rica.